2020
DOI: 10.3390/jcm9103130
|View full text |Cite
|
Sign up to set email alerts
|

Topical Propranolol Improves Epistaxis Control in Hereditary Hemorrhagic Telangiectasia (HHT): A Randomized Double-Blind Placebo-Controlled Trial

Abstract: Epistaxis is a common debilitating manifestation in hereditary hemorrhagic telangiectasia (HHT), due to mucocutaneous telangiectases. The epistaxis can be difficult to control despite available treatments. Dysregulated angiogenesis has been shown to be associated with telangiectases formation. Topical propranolol has demonstrated antiangiogenic properties. We performed a two-phase study, i.e., a double-blind placebo-controlled phase, followed by an open-label phase. The aim of the study was assessment of safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…One hundred and fifteen studies were excluded because they did not meet the inclusion criteria, resulting in 5 articles to be included (2 case series and 3 randomized control trials [RCT]), totaling 132 patients (Table 1). [9][10][11][12][13] Three studies evaluated propranolol and 2 assessed timolol. In the 3 RCTs, 29 participants received topical timolol as a spray, 11 10 received topical propranolol as a gel 12 and 14 received topical timolol as a gel, 13 respectively.…”
Section: Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and fifteen studies were excluded because they did not meet the inclusion criteria, resulting in 5 articles to be included (2 case series and 3 randomized control trials [RCT]), totaling 132 patients (Table 1). [9][10][11][12][13] Three studies evaluated propranolol and 2 assessed timolol. In the 3 RCTs, 29 participants received topical timolol as a spray, 11 10 received topical propranolol as a gel 12 and 14 received topical timolol as a gel, 13 respectively.…”
Section: Searchmentioning
confidence: 99%
“…Mei-Zahav et al found a significant improvement in both their case series (9.4 ± 3.1 to 11 ± 1.8 g/dL, P = .043) 10 and RCT (10.5 ± 2.6 to 11.4 ± 2.02 g/dL, P < .001). 12 Both studies assessed propranolol gel. Peterson et al and Dupuis-Girod et al both used timolol (gel and spray, respectively), and neither demonstrated a statistically significant difference in hemoglobin levels between study groups.…”
Section: Interventionsmentioning
confidence: 99%
“…The severity of epistaxis and the number of blood transfusions pre-and post-administration were reduced rapidly and significantly [39]. As continuation of this study, the same group successfully finished a recent double-blind placebo-controlled study to assess the efficacy and safety of topical propranolol for moderate-severe epistaxis in 24 HHT patients [40].…”
Section: Hereditary Hemorrhagic Telangiectasia (Hht)mentioning
confidence: 88%
“…Patient support groups/patient associations are proven to be very effective in helping all rare disease patients, in general, to better cope with their illness; unfortunately, in our case, the patient did not agree to be referred to a rare disease organization and no specific HHT patient group was locally available. The current guidelines for the approach to HHT [ 10 , 63 ] and research evidence show a broadening spectrum of therapeutic solutions like well-known or repurposed drugs (including bevacizumab, propranolol, pazopanib, tacrolimus, and antithrombotic drugs) and new surgical techniques [ 64 , 65 , 66 , 67 , 68 , 69 ]. These would require more supporting evidence on efficacy and standardized algorithms for clinical use.…”
Section: Discussionmentioning
confidence: 99%